A Study of Different Doped Metal Cations on the Physicochemical Properties and Catalytic Activities of Ce20M1Ox (M=Zr, Cr, Mn, Fe, Co, Sn) Composite Oxides for Nitric Oxide Reduction by Carbon Monoxide. Issue 15 (20th July 2016) - Deng, Changshun; Li, Min; Qian, Junning; Hu, Qun; Huang, Meina; Lin, Qingjin; Ruan, Yongshun; Dong, Lihui; Li, Bin; Fan, Minguang
Abstract: This work is mainly focused on investigating the effects of different doped metal cations on the formation of Ce20 M1 O x (M=Zr, Cr, Mn, Fe, Co, Sn) composite oxides and their physicochemical and catalytic properties for NO reduction by CO as a model reaction. The obtained samples were characterized by using N2 physisorption, X‐ray diffraction, laser Raman spectroscopy, UV/Vis diffuse reflectance spectroscopy, inductively coupled plasma atomic emission spectroscopy, X‐ray photoelectron spectroscopy, temperature‐programmed reduction by hydrogen and by oxygen (H2 ‐TPR and O2 ‐TPD), in situ diffuse reflectance infrared Fourier transform spectroscopy, and the NO+CO model reaction. The results imply that the introduction of M x + into the lattice of CeO2 increases the specific surface area and pore volume, especially for variable valence metal cations, and enhances the catalytic performance to a great extent. In this regard, increases in the oxygen vacancies, reduction properties, and chemisorbed O2 − (and/or O − ) species of these Ce20 M1 O x composite oxides (M refers to variable valence metals) play significant roles in this reaction. Among the samples, Ce20 Cr1 O x exhibited the best catalytic performance, mainly because it has the best reducibility and more chemisorbed oxygen, and significant reasons for these attributes may be closely related to favorable synergistic interactions of the vacancies and near‐surface Ce 3+ and Cr 3+ . Finally, a possible reaction mechanism was tentatively proposed to understand the reactions. Abstract : Just say NO : The effects of different doped metal cations on the formation of Ce20 M1 O x (M=Zr, Cr, Mn, Fe, Co, Sn) composite oxides and their physicochemical and catalytic properties for the reduction of NO by CO as a model reaction are studied. The introduction of M x + into the lattice of CeO2 increases the specific surface area and pore volume, especially for variable valence metal cations, and significantly enhances the catalytic performance.